2006
DOI: 10.1111/j.1551-2916.2005.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution and Formation Mechanism of the Interface Between Titanium and Zirconia Annealed at 1550°C

Abstract: The diffusional reaction between titanium and zirconia was carried out isothermally at 1550°C in argon. The distinct reaction layers in the reaction‐affected zone between Ti and ZrO2 were investigated using analytical scanning electron microscopy, analytical transmission electron microscopy, and electron probe microanalyses. In the metal side, there existed five reaction layers in a sequence of α‐Ti(O), Ti2ZrO+α‐Ti(O, Zr), Ti2ZrO+α‐Ti(O, Zr)+β′‐Ti (O, Zr), α‐Ti (O, Zr)+β′‐Ti (O, Zr), and β′‐Ti (Zr, O) after co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 16 publications
4
37
1
Order By: Relevance
“…At a higher magnification, it was seen that the amount of acicular a-Ti(Zr, O) gradually decreased toward the original interface. 13 Lin and Lin 13 indicated that the acicular a-Ti was precipitated from the b 0 -Ti matrix by means of the ledge mechanism. In contrast, the reaction layer ''III'' was not found after annealing at 11001 or 13001C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At a higher magnification, it was seen that the amount of acicular a-Ti(Zr, O) gradually decreased toward the original interface. 13 Lin and Lin 13 indicated that the acicular a-Ti was precipitated from the b 0 -Ti matrix by means of the ledge mechanism. In contrast, the reaction layer ''III'' was not found after annealing at 11001 or 13001C.…”
Section: Resultsmentioning
confidence: 99%
“…1(d), consisting of b 0 -Ti and the lamellar Ti 2 ZrO1a-Ti. The microstructural development on annealing at 15501C and after subsequent cooling has been described previously 11,13 and schematically shown in Fig. 7(d).…”
Section: (2) Temperature Effect On Microstructural Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of the ''Ti 2 ZrO'' u-oxide is well-established experimentally [13,14,[22][23][24][25][26], although its existence is not widely appreciated. Domagala et al reported a study of the pseudobinary Ti-ZrO 2 phase diagram, showed ZrO 2 to be highly soluble in Ti, and reported the existence of a distinct binary oxide [22].…”
Section: The U-oxidementioning
confidence: 99%